Pengaruh Literasi Keuangan, Pendapatan dan Persepsi Risiko terhadap Konsumen Pinjaman Online di Kota Mataram - Yanti, Hana Putri; Widiyasti, Baiq Dinna; Talidobel, Susilo; Hendri, Wira; Nirwana, Baiq Nadia (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2025)
The advancement of digital technology has driven the growth of online lending services, making them increasingly accessible particularly to Generation Z, who are known for their adaptability to technology. However, this convenience is not always accompanied by adequate financial understanding, which may lead to financial risks. This study aims to determine the influence of financial literacy, income, and risk perception on the use of online loans among Generation Z in Mataram City. The research employs a quantitative approach using an associative method. The sampling technique used is purposive sampling, with a total of 100 respondents who are members of Generation Z and have used online lending services. Data were collected through online questionnaires and analyzed using multiple linear regression analysis. The results indicate that, partially, financial literacy and risk perception have a positive and significant influence on online loan usage, and income also has a significant effect. Simultaneously, all three variables have a significant impact on the use of online loans. These findings highlight the importance of improving financial literacy and risk awareness to prevent the excessive use of online lending among Generation Z. This research is expected to serve as a reference for educational institutions, fintech service providers, and policymakers in formulating effective and sustainable financial education programs and policies.